The Effectiveness of Anti-Mosquito Aromatherapy Candles Formulated with Pine Leaf and Tuberose Flower Essential Oils - Febby A. Elvita; Siti Nuryanti; Dewi S. Ahmar; Ijirana Ijirana; Purnama Ningsih (Jurnal Akademika Kimia, 2025)
The essential oil of tuberose flowers has a distinctive aroma that mosquitoes dislike and can kill insects, and it also contains eugenol, a beneficial antioxidant. Therefore, this essential oil is utilised in aromatherapy candles. Another essential oil with a distinctive aroma is pine needle oil. Its aroma can relieve cold symptoms and also repel mosquitoes. The objective of this research is to determine the characteristics and effectiveness of essential oil extracts from pine needles (Pinus merkusii) and tuberose flowers (Polianthes tuberosa L) as anti-mosquito aromatherapy candles. The research method used is true experimental. The samples used in this study are pine leaves and tuberose flowers. Fresh pine leaves are steam-distilled, while tuberose essential oil is commercially produced. Then, an evaluation stage of the aromatherapy candle preparation is conducted. The results of the therapeutic effect test on F1 and F4 show a feeling of relaxation and freshness. The percentage of mosquito mortality in formulations F0, F1, F2, F3, and F4 were 0%, 27%, 37%, 43%, and 53% respectively. From these formulations, it can be concluded that F0, F1, F2, and F3 are not effective at killing mosquitoes, as only F4 meets the lethal concentration 50 (LC50) criteria. This shows that in the F4 formulation, the essential oil content, consisting of eugenol and α-pinene, produces the highest mosquito mortality rate, and this combination has the potential to be used as an anti-mosquito aromatherapy wax.